Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 5 - Polynomials and Factoring - 5.7 Solving Quadratic Equations by Factoring - 5.7 Exercise Set - Page 351: 29


$t=\left\{ -6,0 \right\}$

Work Step by Step

Factoring the given equation, $ 6t+t^2=0 ,$ results to \begin{array}{l}\require{cancel} t(6+t)=0 .\end{array} Equating each factor to zero (Zero Product Principle), then the solutions to the equation, $ t(6+t)=0 ,$ are \begin{array}{l}\require{cancel} t=0 ,\\\\\text{OR}\\\\ 6+t=0 \\\\ t=-6 .\end{array} Hence, $ t=\left\{ -6,0 \right\} .$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.